INTERPRETATION OF THE TEXT AS A SUBJECT: ITS AIMS AND TASKS, AND ITS LINKS WITH OTHER SUBJECTS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Text interpretation is one of the central areas of stylistics that focuses on the comprehensive analysis of linguistic, semantic, and pragmatic features of a text. It aims to uncover both explicit and implicit meanings, identify stylistic devices, and understand the communicative intention of the author. The subject develops students’ analytical and critical thinking skills, enabling them to interpret texts effectively in various contexts. Additionally, text interpretation is closely interconnected with disciplines such as linguistics, literary criticism, discourse analysis, psychology, and cultural studies. This interdisciplinary approach broadens the scope of stylistic analysis and enhances deeper understanding of texts.